Carrier Frequency offset (CFO) Estimation in MC-CDMA System - Dr. GuntuNooka Raju, Dr.PMK Prasad, Bethapudi Ratnakanth (International Journal of Advanced Science and Technology, 2020)
Wireless communications is a broad, dynamic and the fastest growing sector of communication industry for the past several years. In this regime, numerous research efforts are underway to improve the performance efficiency and effectiveness of several multiple carriers multiple access model at various phases. Multicarrier code division multiple access (MC-CDMA) model is one such approach, defined as the frequency dependent multiple access architecture that merges the features of FDMA and CDMA to concurrently exploit frequency assortment and diminish carrier frequency offset (CFO) at MC-CDMA receiver model.In this regards, this paper proposed novel schemes to enhance the performance of both MC-CDMA transmitter and receiver model. In addition, the effect carrier frequency offset (CFO) on Multi-Carrier systems has degraded the performance of the system; therefore, it is essential to estimate of CFO and minimize its influence on multiple carrier modulations systems using different estimation techniques. Keywords: Carrier frequency offset, MC-CDMA system, MSE, Cyclic Prefix (CP),Symbol, Pilot tone estimation.